THE IMPACT OF THE THINK PAIR SHARE STRATEGY ON STUDENTS’ SPEAKING SKILL - Hakim, Wisda; Ugahara, Ugahara; Dauyah, Ema; Syahabuddin, Khairiah (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
The purpose of this research is to determine the impact of the Think-Pair-Share strategy on students' speaking skill. The research method employed a quantitative approach with a quasi-experimental design. Pre-test and post-test were used as instruments in this study to measure the development of students' speaking abilities. The sample size for both the controlled and experimental classes consisted of 25 students. The results of this research depict significant findings. The consistent use of the Think-Pair-Share strategy led to a meaningful improvement in the speaking abilities of the tenth-grade students at MAS Dayah Darul Ihsan. During the research period, students showed a noticeable enhancement in their ability to communicate more confidently and effectively. This is evidenced by the final scores in the experimental class, which were 72.92, while the controlled class scored 56.88. Therefore, it can be concluded that by providing opportunities for students to interact, discuss, and share ideas, the use of this strategy not only enhances their speaking abilities but also boosts their self-confidence in communication. Thus, the Think Pair Share strategy holds great potential for improving students' speaking abilities in various educational settings.